Does practising hypnosis-derived communication techniques by oncology nurses translate into reduced pain and distress in their patients? An exploratory study. Issue 2 (May 2021) - Ogez, David; Aramideh, Jennifer; Mizrahi, Terry; Charest, Marie-Claude; Plante, Caroline; Duval, Michel; Sultan, Serge
Objectives: To explore the effects of a hypnotic communication (HC) training for paediatric nurses in decreasing patients' pain and distress during venipunctures. Methods: A 4-day theoretical and practical HC training was offered to five paediatric oncology nurses. The effects of HC were tested with 22 young cancer patients (13 girls, 9 boys, 10 ± 4 years) over four time points, with 88 encounters being video-recorded and coded in stable professional-patient dyads. Patients' pain and distress were rated by patients and parents with visual analogue scales and coded from recordings using the Faces, Legs, Activity, Cry and Consolability (FLACC) scale. Results: We observed a significant decrease in pre-post distress reported by parents ( d = 0.45, p = 0.046). Two out of five nurses with higher skills acquisition had larger reduction in patients' self-reported pain ( d = 1.03, p = 0.028), parents perceived pain ( d = 1.09, p = 0.042), distress ( d = 1.05, p = 0.043) as well as observed pain ( d = 1.22, p = 0.025). Favourable results on pain and distress did not maintain at follow-up. Conclusion and clinical implications: Training nurses in HC may translate into improved pain and distress in patients, both self-rated and observed provided that skills are used in practice. HC training is a promising non-pharmacological intervention to address pain in paediatrics.